NIVEL DE ATIVIDADE FÍSICA EM ATLETAS DE FUTSAL (Fiep Bulletin - online, 2017)
Physical Activity Level in Futsal AthletesObjective: The objective of this study was to evaluate the level of physical activity of university athletes participating inthe UFMA Men's Open Futsal Cup in 2015. Materials and Methods: This study was conducted with 20 athletes participating in theUFMA Open Futsal Men's Cup in 2015. The instrument used was the International Physical Activity Questionnaire (IPAQ), longversion and the procedure was as follows: The athlete was asked to read and complete the questionnaire in the pre-match courtenvironment. In this study we used the descriptive statistics. Results and Discussion: According to the analysis of thequestionnaire we can affirm that 60% of the athletes that participated in the Open Cup of Futsal 2015 are active and 25% with veryactive classification thus demonstrating an excellent level of physical activity. Conclusion: In this way, those sampled formaintaining a high standard of physical activity.
Keywords: Futsal; Physical Activity; Young